Interventional left atrial appendage closure affects the metabolism of acylcarnitines - Fastner, Christian; Behnes, Michael; Sartorius, Benjamin; Wenke, Annika; Lang, Siegfried; Yücel, Gökhan; Sattler, Katherine; Rusnak, Jonas; Saleh, Ahmad; Barth, Christian; Hoffmann, Ursula; Borggrefe, Martin; et al. (International journal of molecular sciences, 2018)
Background: Left atrial appendage closure (LAAC) represents the interventional alternative to oral anticoagulation for stroke prevention in atrial fibrillation (AF). The metabolism of acylcarnitines was shown to affect cardiovascular diseases. This study evaluates the influence of successful LAAC on the metabolism of acylcarnitines. Methods: Patients undergoing successful LAAC were enrolled prospectively. Peripheral blood samples for metabolomics measurements were collected immediately before (i.e., index) and six months after LAAC (i.e., mid-term). A targeted metabolomics analysis based on electrospray ionization-liquid chromatography-mass spectrometry (ESI-LC-MS/MS) and MS/MS measurements was performed. Results: 44 patients with non-valvular AF (median CHA2DS2-VASc score 4, median HAS-BLED score 4) and successful LAAC were included. Significant changes in acylcarnitine levels were found in the total cohort, which were mainly attributed to patients with impaired left ventricular and renal function, elevated amino-terminal pro-brain natriuretic peptide (NT-proBNP) and diabetes mellitus. Adjusted multivariable regression models revealed significant changes of five metabolites over mid-term follow-up: C2, C14:1, C16, and C18:1 decreased significantly (each p < 0.05); short-chain C5 acylcarnitine plasma levels increased significantly (p < 0.05). Conclusion: This study demonstrates that successful LAAC affects the metabolism of acylcarnitines at mid-term follow-up.
Gesehen am 07.10.2019